The role of change management in trust formation in commercial banks - Iljins, Juris; Skvarciany, Viktorija (Business: Theory and Practice, 2015)
Trust in commercial banks is considered to be one of the vital factors affecting the success of commercial banks’ activities. However, the level of trust in banks has decreased during last years and is quite low at present. Therefore, it is necessary to change the confidence level to higher. This scientific paper focuses on the ways of managing and changing business process to increase trust in banks through change management. To distinguish the factors of trust formation the qualitative research has been conducted. After summarizing the results of the survey seven factors of trust building were identified. To determine the factors of change management influencing trust formation the expert evaluation method was used, six main factors were distinguished, and relations between key impact factors were defined. As a result, the model of change management factors influencing the trust formation in commercial banks has been created. In other words, the model shows how change management factors could influence the change in trust level from low to higher one and, hence, to increase bank’s competitiveness.